The Relationship Between Ethical Leadership and Employee Job Satisfaction: The Mediating Role of Media Richness and Perceived Organizational Transparency - Guo, Kaimeng (Frontiers in Psychology, 2022)
Ethical leadership is a vital component driving firms' practice, significantly affecting employee satisfaction. The study objective is to investigate the relationship between ethical leadership and employee job satisfaction. Moreover, the study investigates the mediating effect of media richness, perceived organizational transparency on ethical leadership, and employee satisfaction. Also, the study used a convenient sampling technique for collecting the data from 276 employees working in the service sector of Macau. Essentially, questionnaires had used as the fundamental tool guiding the data collection method. The findings indicate a positive and significant relation between ethical leadership, employee’s satisfaction, media richness, and perceived organizational transparency. The media richness and perceived organizational transparency have significant mediating effects between ethical leadership and employee’s satisfaction. The study is beneficial for the services sector of Macau to plan the strategies for their employees in terms of organizational sustainability and success. The study is also helpful for the government to understand ethical leadership and for the researcher to search the new aspects of ethical leadership in organizations for future research direction.